The Environmental Consequences of Global Reuse - Kinnaman, Thomas; Yokoo, Hide-Fumi (American Economic Review, 2011)
This paper summarizes a two-country model that solves for optimal tax rates to achieve efficiency in an economy with international trade in used consumer electronics. If only the developed nation can tax the disposal of e-waste, then the global Pareto Optimum can be obtained by either imposing an import tariff on used consumer electronics or subsidizing the return of e-waste for disposal in the developed country. The global Pareto Optimum can also be obtained by reducing the disposal tax in the developed country to a level below the external marginal cost of disposal should no other policy option be available.